Formation of the System of Threats to Energy Security of the Republic of Belarus - E. P. Korsak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The energy sector of the Republic of Belarus is one of the key sectors of the national economy, the effective development of which ensures the operation of the entire real economy and the sphere of housing and communal services. Due to the lack of the necessary amount of its own energy resources, the country is affected by factors of internal and external threats that form the energy dependence of the Republic on the supply of fuel and energy resources from outside. This weakens its energy security. The main importing country of fuel and energy resources for the Republic of Belarus is the Russian Federation. In this regard, the concept of energy security needs to be clarified, taking into account external and internal threats. The article deals with theoretical approaches to the definition of energy security, the specific features for the importing and exporting countries. The main threats to energy security for the Republic of Belarus are clarified, the causes of their occurrence and consequences for both fuel and energy complex enterprises and energy consumers are revealed. To determine the level of energy security, the indicative assessment method, which involves the identification of parameters and indicators of the development and functioning of the fuel and energy complex, its subsystems and facilities, as well as energy consumers, is the most optimal. These parameters characterize the composition, depth and territorial framework for the implementation of threats to energy security, its level. The indicators of the main directions of energy safety have been analyzed in dynamics; their levels are determined by periods. The directions of energy security, which are most and least susceptible to threats, have been identified. A combined approach for determining the objects of energy security is proposed. The author's definition of energy security is presented.